Manifestations of sustainable development in the social policies of Dubai smart city: a qualitative study - Sajwani, Ghayath; AlOthman, Hussain (Al-Adab Journal, 2023)
The city of Dubai is a model for smart city policies that help understand rapid development. Dubai, with its vision, has tried to follow the footsteps of sustainable cities. This study took into account some of what contributed to the success of sustainable development in general and social sustainability in particular in Dubai. Whereas, this qualitative study looked at the social dimensions and the influences on their sustainability, such as popular participation, human capital, and the reduction of social disparities. Through this study, the sustainability of Dubai was identified through the impact of sustainable policies on people for the social dimension and their opinion on the current situation. The research found that Dubai is on the line of social sustainability because of its many and varied initiatives, but there are many challenges, including the need to pay attention to the family, better education and more awareness in terms of the importance of the social dimension and sustainability. As well as paying attention to reducing the gap between rich and poor as a social difference, and sharing people’s opinion on future strategie.